Perioperative management of a patient with myasthenia gravis: a case report, treatment of myasthenic crisis and literature review - O.Yu. Usenko; A.V. Sydiuk; O.Ye. Sydiuk; V.V. Antonenko; G.Yu. Savenko; O.T. Teslia; А.А. Dykan; S.I. Chechil (Медицина неотложных состояний, 2025)
Surgical intervention, such as thymectomy, and a comprehensive approach to the treatment of patients with myasthenia gravis can improve the quality and duration of their lives. At the same time, perioperative management should be carefully selected. These patients require attention because of the risk of developing a myasthenic crisis and a complicated recovery from it. Specific attention and care are paid to the administration of any medications, especially neuromuscular blocking agents. Patients with myasthenia gravis, having a pathology of acetylcholine receptors, are unexpec-tedly sensitive to non-depolarising neuromuscular blocking agents and resistant to depolarising succinylcholine.